Heterogeneous Ni3P/Ni nanoparticles with optimized Ni active sites anchored in N-doped mesoporous nanofibers for boosting pH-universal hydrogen evolution. Issue 39 (30th September 2022) - Fu, Changle; Feng, Liangliang; Yin, Hongyan; Li, Yuhang; Xie, Yajie; Feng, Yongqiang; Zhao, Yajuan; Cao, Liyun; Huang, Jianfeng; Liu, Yipu
Abstract : A novel tactic of synergetic electronic coupling is successfully developed for rendering metal-rich phosphides as an efficient pH-universal electrocatalyst for the hydrogen evolution reaction. Abstract : Developing low-cost, environmentally friendly and efficient non-precious metal electrocatalysts as alternatives to noble metals for the hydrogen evolution reaction (HER) is highly essential for the sustainable advancement of green hydrogen energy. Herein, a novel heterostructured Ni3 P/Ni nanoparticle anchored in nitrogen-doped mesoporous carbon nanofibers (Ni3 P/Ni@N-CNFs) is prepared by a facile solid-phase calcination protocol. The results demonstrated that benefiting from the intensive electronic coupling effect at the interface of the Ni3 P/Ni heterostructure, the electron configuration of the Ni active site is optimized and thus the favorable HER activity. Furthermore, the N-doped carbon nanofiber scaffold with an extensive mesoporous structure endows Ni3 P/Ni@N-CNFs with abundant electrochemically active sites together with excellent conductivity and stability, contributing to fast electron/mass transport. As expected, the resultant Ni3 P/Ni@N-CNF electrocatalyst exhibited exceptional HER catalytic properties under universal pH conditions, driving a current density of 10 mA cm −2 at pretty low overpotentials of 121 mV, 145 mV and 187 mV in acidic, basic and neutral solutions, respectively, and retaining the catalytic stability for over 60 h. This intriguing work represents a fresh perspective for designing and exploiting highly advanced phosphide electrocatalysts for green hydrogen fuel production.